Biologic therapies for chronic obstructive pulmonary disease. (1st February 2023) - Matera, Maria Gabriella; Calzetta, Luigino; Cazzola, Mario; Ora, Josuel; Rogliani, Paola
ABSTRACT: Introduction: Chronic obstructive pulmonary disease (COPD) is a disorder characterized by a complicated chronic inflammatory response that is resistant to corticosteroid therapy. As a result, there is a critical need for effective anti-inflammatory medications to treat people with COPD. Using monoclonal antibodies (mAbs) to inhibit cytokines and chemokines or their receptors could be a potential approach to treating the inflammatory component of COPD. Areas covered: The therapeutic potential that some of these mAbs might have in COPD is reviewed. Expert opinion: No mAb directed against cytokines or chemokines has shown any therapeutic impact in COPD patients, apart from mAbs targeting the IL-5 pathway that appear to have statistically significant, albeit weak, effect in patients with eosinophilic COPD. This may reflect the complexity of COPD, in which no single cytokine or chemokine has a dominant role. Because the umbrella term COPD encompasses several endotypes with diverse underlying processes, mAbs targeting specific cytokines or chemokines should most likely be evaluated in limited and focused populations.